1980
DOI: 10.1111/j.1528-1157.1980.tb04320.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional Study on the Teratogenicity and Fetal Toxicity of Antiepileptic Drugs: A Report of a Collaborative Study Group in Japan

Abstract: A multi-institutional collaborative study was conducted concerning the course of pregnancy and delivery and the incidence of abnormal infants delivered of epileptic women. Of 657 women receiving antiepileptic drugs, 73% delivered live infants, 14% had miscarriage or stillbirth, and 13% underwent induced abortion. In contrast to the above findings, 80% of 162 patients not receiving antiepileptic drugs delivered live infants and 4% had miscarriage or stillbirth. The latter outcome was significantly increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
7

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(97 citation statements)
references
References 38 publications
(42 reference statements)
1
88
0
7
Order By: Relevance
“…Certain AED combinations are associated with enhanced risk (e.g., VPA), and an enzyme-inducing AED (e.g., PB, PHT, and CBZ) enhances the risk of malformations and hepatotoxicity and therefore alternative AEDs should perhaps be considered (47)(48)(49). Furthermore, there is evidence to suggest, from a study of a relatively small number of patients receiving polytherapy, that the incidence of malformations increases with increasing number of AEDs; exposure to two, three, or four AEDs is associated with an incidence rate of malformations of 5.5, 11, and 23%, respectively (50). A recent prospective study reported that whereas the odds ratio of malformations for an infant exposed to a single AED was 2.8, the odds ratio for two or more AEDs was 4.2 (51).…”
Section: Pregnancymentioning
confidence: 99%
“…Certain AED combinations are associated with enhanced risk (e.g., VPA), and an enzyme-inducing AED (e.g., PB, PHT, and CBZ) enhances the risk of malformations and hepatotoxicity and therefore alternative AEDs should perhaps be considered (47)(48)(49). Furthermore, there is evidence to suggest, from a study of a relatively small number of patients receiving polytherapy, that the incidence of malformations increases with increasing number of AEDs; exposure to two, three, or four AEDs is associated with an incidence rate of malformations of 5.5, 11, and 23%, respectively (50). A recent prospective study reported that whereas the odds ratio of malformations for an infant exposed to a single AED was 2.8, the odds ratio for two or more AEDs was 4.2 (51).…”
Section: Pregnancymentioning
confidence: 99%
“…Fetal exposure to anticonvulsants has been associated not only with relatively high rates of neural tube defects (NTDs), such as spina bifida, but also with multiple anomalies, including craniofacial abnormalities (also known as the "anticonvulsant face"), congenital heart disease, cleft lip or palate, growth retardation, and microcephaly (76)(77)(78)(79). Factors that may increase the risk for teratogenisis include high maternal serum anticonvulsant levels and exposure to more than a single anticonvulsant (77,(82)(83)(84). The lowest effective dosage should be used, and given in frequent divided doses over the course of the day (85).…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…However other authors -Lindhout and Omtizigt 5 in 1992 -found an absolute risk factor of 7 to 10%, i.e., 3 to 5% higher than that in the general population. The number and doses of AEDs utilized can also interfere with the final result , high doses and polytherapy increasing this risk 6,7 . Anomalies and malformations commonly found in association with the use of AED are: a) neural tube defects -"spina bifida", mostly related to the use of sodium valproate 8 and carbamazepine 9 ; b) facial cleft -labial or palatal 10 and, c) congenital cardiac defects (atrial septal defect, Fallot's tetralogy, ventricular septal defect, aortic coarctation, pulmonary stenosis and persistence of the arterial channel) 11 .…”
mentioning
confidence: 99%
“…Anomalies and malformations commonly found in association with the use of AED are: a) neural tube defects -"spina bifida", mostly related to the use of sodium valproate 8 and carbamazepine 9 ; b) facial cleft -labial or palatal 10 and, c) congenital cardiac defects (atrial septal defect, Fallot's tetralogy, ventricular septal defect, aortic coarctation, pulmonary stenosis and persistence of the arterial channel) 11 . The majority of studies on fetal malformations and AEDs, have been made in patients treated with the five leading AEDs -phenytoin (DPH), carbamazepine (CBZ), phenobarbital (PB), primidone (PR), and sodium valproate (VPA) [4][5][6][7][8][9][10][11] . In general, investigators agree that the risk of fetal malformations due to AEDs is about twofold above normal, and is enhanced by polytherapy and high AED serum levels.…”
mentioning
confidence: 99%